HUBUNGAN AKSES AIR MINUM DAN SANITASI PADA KELUARGA DENGAN KEJADIAN STUNTING: SCOPING REVIEW: THE RELATIONSHIP BETWEEN FAMILY ACCESS TO DRINKING WATER AND SANITATION AND THE INCIDENCE OF STUNTING: A SCOPING REVIEW - Nur'aeni, Nabyla (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: Water and soil have a role in the transmission of disease. Cases of malnourished children under five have the potential to increase due to inadequate latrine facilities and drinking water quality. This review aims to decide the relationship between family access to drinking water and sanitation and the incidence of stunting to analyze the next prevention. Methods: The approach taken is a scoping review by identifying articles in PubMed, CINAHL, and Sage from 2012-2022. The keywords used were "family, clean water and sanitation, stunting" developed with the PICO framework. Result: Five articles were included in the analysis. Three of the five studies concluded a significant association between family access to drinking water and sanitation and the incidence of stunting. This was also related to the management and storage of water for drinking and family hygiene behaviors. Conclusion: Access to drinking water and sanitation is associated with stunting. Interventions are needed not only in infrastructure development to provide access to clean water and affordable latrines but also to increase public awareness.